Impact of small-airway disease on exercise intolerance and long-term outcomes in patients with heart failure and reduced or preserved ejection fraction. (3rd October 2022) - Nagumo, D; Hamazaki, N; Kamiya, K; Obara, S; Kobayashi, S; Nozaki, K; Ichikawa, T; Yamashita, M; Uchida, S; Noda, T; Ogura, K; Maekawa, E; et al.
Abstract: Introduction: Exercise intolerance in patients with heart failure (HF) is a strong indicator of a poor prognosis. As the respiratory impairment in HF patients, the small airway is reportedly more susceptible than central airways, which results in increased airway resistance and may cause poor outcomes. However, the impact of small-airway disease (SAD) on exercise intolerance and prognosis in patients with HF is still unclear. Purpose: We investigated the associations between SAD and exercise intolerance in patients with HF, and the clinical significance of SAD for long-term clinical events with a reduced or preserved ejection fraction. Methods: We reviewed 1015 patients with HF (mean age, 66.9±14.6 years; male, 64.5%) admitted for medical treatment. Patients with a prior history of chronic respiratory disease or an obstructive lung pattern – defined as the forced expiratory volume (%) in 1 s relative to <70% forced vital capacity using spirometry – were excluded. Characteristics including HF aetiology, comorbidities conditions, medications, blood parameters, and echocardiographic variables were obtained from clinical records. All patients underwent spirometry at hospital discharge, and SAD was defined as the maximum mid-expiratory flow (%) relative to a <60% predicted value. At hospital discharge, we measured 6-min walk distance (6MWD), and <300 m was considered as exercise intolerance. The primary endpoint was a composite clinical event of all-cause death and/or unplanned readmission for HF. Multivariate logistic regression analysis was used to assess the association between SAD and exercise intolerance. The multivariate Cox proportional hazard model was used to clarify whether SAD was an independent predictor for the incidence of clinical events. We also performed subgroup analyses in each multivariate analysis based on a left ventricular ejection fraction (LVEF) of 40%. Result: SAD was observed in 479 (47.2%) patients. LVEF subgroups included 458 (45.1%) and 518 (51.0%) patients with LVEF <40% and ≥40%, respectively. After adjusting for clinical characteristics, SAD was independently associated with 6MWD <300 m (Figure 1). Moreover, this association was consistently observed in the LVEF <40% and ≥40% (Figure 1). During the median follow-up period of 1.5 years, all-cause death/readmission occurred in 431 patients (42.5%), and the incidence rate was 17.5/100 person-years. In the multivariate Cox proportional hazard model, SAD was independently associated with lower event-free survival rates in all patients and the LVEF <40% subgroup, but not LVEF ≥40% subgroup (Figure 2A, B, and C, respectively). Conclusion: This study is the first to reveal that SAD is associated with exercise intolerance in patients with HF regardless of LVEF. Moreover, SAD may have a predictive significance for long-term outcomes in patients with HF and subgroups with reduced, but not preserved ejection fraction. Funding Acknowledgement: Type of funding sources: None.